Causes of Conflict in Sudan: Testing The Black Book. - Cobham, A (Nuffield College (University of Oxford), 2005)
The Black Book of Sudan claims to identify a pattern of political control--by people of its northern regions--which is unbroken during the post--independence period. This is the basis for the view of many of the rebel groups in the country that their conflicts are the result not only of racial or religious discrimination but also importantly of regional marginalisation. This paper uses the available data to evaluate the performance of the current regime, and finds that policy has systematically undermined the human development of the population of the marginal regions, not least Darfur.